Culinary Satisfaction in Jakarta's Old Town: The Roles of Product Quality and Administrative Service Innovation - Andi Nuralim Kamal; Retno Kusumastuti (International Journal of Economics Development Research (IJEDR), 2023)
This research explores the impact of product quality and administrative service innovation on customer satisfaction in the culinary sector of Jakarta's Old Town. Employing a quantitative methodology, the study uses a questionnaire to gather data from a diverse group of customers in the area. The demographic analysis of respondents highlights a predominance of female participants, largely falling within the 21-35 years age group, and primarily students.  The study demonstrates that both product quality and administrative service innovation significantly contribute to customer satisfaction, both individually and collectively. These findings suggest that improving product quality and cultivating innovative administrative services can effectively enhance customer satisfaction in the culinary sector. Moreover, the research concludes that a substantial proportion of the variation in customer satisfaction can be explained by these two factors, with the remainder attributed to other variables not examined in this study. These insights are envisaged to guide culinary industry players in Jakarta's Old Town in devising more effective marketing strategies. The research also underscores the need for further studies to explore other potential factors influencing customer satisfaction in the culinary sector.